Cultura organizacional e cultura local frente a frente: um estudo junto a organizações localizadas em Montes Claros, Minas Gerais - Maria de Fatima Pinho Godinho (2000)
The aim of this study was to determine whether a compatibility exists between organizational and local cultures and which features of local culture integrate human resource strategies. When focusing on spheres of organizational and local cultures it is assumed that both have interrelated patterns, which influence each other and also that they share significantly important practices that define the universe of organizations.Two organisations from Montes Claros, Minas Gerais, were used as case study. The analyses were constituted of a descriptive qualitative investigation that included testimony of employees, company documents and bibliographic searches. The results indicate the existence of two different cultural universes. This confirms the fact that environmental requirements, forms of domination, history of the organization and characteristics of the staff confer each organization a singular configuration and influence both individual and group behavior.